State of the art, propagation and conservation of Juglans neotropica Diels., in Andean zones - Toro Vanegas, Esaú; Roldan Rojas, Isabel Cristina (Instituto de Ecología, A.C., 2018)
The species of the family Juglandaceae have evolved along 56 million years, being distributed all over the world. Juglans neotropica is native to South America; it is found from 1800 m to 2800 m in altitude, in dry and humid low montane forests. It is a species of alternate composite leaves, monoecious, with cross-pollination and anemophilous, dispersed by animals and water, with annual reproduction. Currently, it is cataloged in danger of extinction (EN A2cd) since 52% of its populations are over exploited for purposes of producing timber. The uses of the species make it promising; its wood is one of the most valuable in the world because of the fact that active substances with potential for the textile industry, medicine and human food have been found in all of its parts; it has been used as an excellent source of firewood in rural areas. This species is key in the adaptation to the climate change because of its environmental services in the ecological recovery of degraded soils, and for maintaining the quality of air and water under agroforestry systems that, at the same time, are a habitat and source of food resources for wildlife. Also it is important as ornamental in urbanized Andean landscapes. Because of all  those arguments, a propagation proposal is made as a conservation measure in Andean zones, based on documented studies for the species.